Pathogenic and molecular variability and telia production of uromyces appendiculatus isolates from the andean and Middle American centers of domestication of common bean - Araya Fernández, Carlos Manuel ([editor no identificado], 1996)
tesis (Doctor of Philosophy)--University of Nebraska, 1996.